Exploring the effects of inclusion of dietary fresh Azolla on the performance of White Pekin broiler ducks - Acharya, Parag (Vet World, 2015)
AIM: The objective of this study was to investigate the dietary advantages of inclusion of unconventional nutrient source, i.e., Azolla in the basal diet of White Pekin broilers. MATERIALS AND METHODS: All ducklings were randomly distributed into three treatment groups with three replicates each and each replicate having 12 ducklings and were reared in deep litter system. Groups were subjected to three dietary treatments such as G(1): Basal diet, G(2): Basal diet + 5% fresh Azolla of basal diet, G(3): Basal diet + 10% fresh Azolla of basal diet. During experimental period, parameters, such as bodyweight, bodyweight gain, feed consumption,feed conversion ratio(FCR), and economic of production,wererecorded. RESULTS: The result showed that body weights in every week, except the 5(th) week, did not differ significantly between groups. However, no significant difference was observed between the groups in any week in terms of absolute body weight gain and feed consumption. As regard to FCR, the 10% Azolla group (G(3)) showed the best feed efficiency followed by the 5% Azolla group (G(2)) and the control group (G(1)). On the basis of profit/bird or profit/kg live weight, each of the Azolla-fed group showed a higher economic efficiency than the control. CONCLUSION: From the experiment, it was concluded that Azollaat 5 or 10% level can be included in the diet to economize the White Pekin broiler farming, and it can be great impetus to poultry farming to include unconventional nutrient source as a dietary supplement.